Disputes on women’s deaconate in the Church of England - Artem Kokosh (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
In the history of the Anglican Church the top-ranked issue of the second half of the 20th century and the beginning of the 21st century was disputes on women’s priesthood. As a result of these debates, the Anglican Church began to ordain women as deacons, then as priests, and finally as bishops. In Orthodox view, it was the radical change of the doctrine and the deviation from the apostolic tradition, though at the beginning of the 20th century the Anglican Church was considered as one of the closest churches to Orthodoxy. The first critical step in the direction of women’s priesthood was the opening the diaconate to women. Both in Russian and Western theological science little attention has been devoted to the analysis of this first step, since historically the hottest theological discussion was on the issue of women’s priesthood and women’s episcopate. However, the decision on women’s diaconate was very important since it actually opened the way for all subsequent decisions on women’s priesthood in the Anglican Church. This article offers an analysis of the historical processes and theological discussions that brought the Church of England to the appearance of deaconesses and then women deacons. The article considers the revival of sisterhoods and monastic communities in the Church of England in the middle of the 19th century, the initiative to revive the rank of deaconesses in 1862 and subsequent official decision of the 1920 Lambeth Conference, as well as the relevant reports of the Commissions of 1897, 1908, 1919 and 1935. Then we analyze the discussions about the functions of the deaconess, as well as additional factors that influenced the decision to allow women to be ordained as deacons. One of these factors was the general crisis of the diaconal ministry and the desire to strengthen the role of the laity in the life of the Anglican Church. As a result, the 1968 Lambeth Conference opened diaconate to all laymen remaining in secular occupations (both men and women). The Church of England turned out to be one of the most conservative churches in the Anglican Communion – it introduced women's diaconate almost 20 years later, in 1987. Conservative groups were concerned that this decision would put the Church of England on a "slippery slope" towards women's priesthood and women's episcopate. Subsequent history proved that these fears were completely justified.